Teachers' Instructional Practices and Mathematics Performance: A Correlational Study in Ogun State Secondary Schools, Nigeria - Oluwadayo, Abiodun Taiwo (Indonesian Journal of Education and Social Sciences, 2026)
This study examined Teachers' Instructional Practices and Mathematics Performance: A Correlational Study in Ogun State Secondary Schools, Nigeria. A correlational research design was employed in the study. Two research questions guided the study. The study's population consisted of all students at Senior Secondary School Two (SSS2) in Ogun-East Senatorial District, Ogun-State, Nigeria. Thirty (30) mathematics teachers and four-hundred (400) students made up the total sampled respondents. The participants were chosen using simple random sampling technique. Questionnaire on Teachers’ instructional practices (QIP) with reliability, r = 0.84 using Cronbach's alpha technique, and Mathematics Achievement Test (MAT) with reliability, r = 0.76 using Kuder Richardson formula 20 (K-R20) were used to collect data. Multiple Regression Analysis (MRA) and Pearson Product Moment Correlation (PPMC) were used as inferential statistics to analyze the data at the 0.05 level of significance. According to the study's findings, students' academic performance in senior secondary school mathematics was significantly predicted by the levels of teachers’ assessment, lesson-plan, classroom management, teaching methods.